SOCIAL PRESENCE AND REPURCHASE INTENTION IN SOCIAL COMMERCE PLATFORMS: THEORETICAL REVIEW - Jiao Ying Da; Ooi Boon Keat (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to investigate how social commerce, as a subset of online buying integrated with social media interaction, influences consumer behaviors such as repurchase intention and active engagement. Method: The research framework is grounded in Social Exchange Theory (SET) and the Theory of Planned Behaviour (TPB), examining the relationships among social presence, trust, and customer engagement. Results: Findings indicate that social presence—defined as the perception of warm, personal, and authentic connections—plays a pivotal role in fostering trust, reducing online transaction risks, and enhancing customer loyalty. Furthermore, increased engagement within social commerce platforms was found to strengthen community growth and brand attachment, ultimately driving sustainable repurchasing behaviors. Novelty: This study contributes by addressing a critical gap in the literature concerning retention and loyalty beyond initial adoption, offering both theoretical insights and practical strategies for cultivating genuine online communities that transform satisfied consumers into long-term brand advocates.